THE RELATIONSHIP BETWEEN COMPETITIVE TENDERING METHODS AND QUALITY OF SERVICE DELIVERY IN WAKISO DISTRICT: A CORRELATIONAL STUDY. - Nakulima, Mariam; Ssendagi , Mohammad (Student's Journal of Health Research Africa, 2024)
Background: The study aims to assess the relationship between competitive tendering methods and the quality of service delivery in Wakiso District. Methodology: This study was guided by a cross-sectional correlational research design. Triangulation of research methods was adopted in this study. 68 participants formed the sampling framework and 65 of them were determined as the sample. The sample was reached using simple random sampling techniques and purposive sampling techniques. With the quantitative data, analysis was done using frequencies, percentages, means, and Pearson correlation matrix. On the side of qualitative data, was analyzed using Content analysis. Result: Most of the participants were males (54%), between the ages of 40-49 years (58.8%), with an educational level of a Bachelor’s degree (58.8%), and having worked in Wakiso district user departments for 4-6years (44.1%). It was established that competitive tendering was significantly related to the quality of service delivery in Wakiso District. This is based on the Pearson value which was established at r=0.700 which was significant P=0.019. This was measured at less than 0.05 (level of significance). This meant that the higher the practice of competitive tendering, the higher the improvement in the quality of service delivery in Wakiso District. Conclusion: Quality of service delivery is highly determined by the proper application of competitive tendering methods in Wakiso District. Recommendation: National suppliers or service providers must be given a chance to undertake procurement opportunities. This can be done by ensuring that local companies that have acquired some expertise are considered without being compared to international companies.